The role of self-congruity theory in consumer’s evaluation of tourism destinations - Gyulavári, Tamás; Malota, Erzsébet (The Hungarian Journal of Marketing and Management, 2019)
The main purpose of our study was to investigate the effect of congruence between the perceived self-image and the country’s culture - personality on the evaluation of the country as a touristic destination among young consumers. The role of personality often emerges in branding studies and nowadays also in country branding, more and more scales has been published to measure this specific concept. For our research, we applied two theoretical approaches based on the relevant literature. On the one hand, according to the self-esteem enhancing mechanism, we find products and services (or countries) attractive, if we perceive their image and personality more positively than our self- image. On the other hand, according to self-consistency, motivations for self-expression make us look for brands (in our case country destinations) expressing our own personality. Our results prove that perceived personality should be taken into consideration in branding strategy of destinations, and the effect of self-esteem enhancing mechanism is stronger than the self-expression mechanism.